Isolation, Partial Purification and Median Lethal Dose of Antipyretic Agent from Khaya senegalensis Leaf Extracts - Ibrahim Sani; Angela Nnenna Ukwuani-Kwaja; Timothy Eromosele Ehebha (Newinera Publisher, 2021)
This research was designed to evaluate the antipyretic activity of K. senegalensis leaf extract with the view of isolating and identifying the active components. The K. senegalensis leaf was extracted using 90% methanol and further fractionated with hexane, ethylacetate, n-butanol and distilled water.The qualitative phytochemical screening was carried out using standard methods.The crude extract and the fractions were screened for antipyretic activity using 15%w/v brewer’s yeast induced pyrexia on Albino rats. The components of the most active fraction were further separated using column and thin layer chromatographic techniques on silica gel. LD50 of the most active fraction was determined using probit analysis. The results of the phytochemical screening revealed the presence of tannins, phenols, steroids and cardiac glycosides in both the crude extract and its fractions. The crude extract at 400 mg/kg b.w. showed the highest antipyretic activity compared to the other doses tested. Hexane fraction showed the highest antipyretic activity among the other fractionated extracts. The LD50 of the hexane fraction was found to be 831.76 mg/kg b.w. The column chromatographic separation of the hexane extract yielded 60 fractions (F1 to F60). After TLC separation, fractions with similar profile were pooled together yielding eleven (11) pooled fractions (PF1 to PF11). Antipyretic activities of the pooled fractions showed that PF8 exhibited the highest activity. These findings suggested that, K. senegalensis leaf has significant antipyretic activity which can be considered for the development of antipyretic agent from natural resources.